Ambivalences orientalistes : économie chilienne et marchés asiatiques, 1900-1940 - Pedro Iacobelli (Cahiers des Amériques Latines)
Despite the great economic importance of East Asia in Chile, Asianness tends to remain in a state of conditioned visibility and subject to discourses of otherness. This research studies the origins of the perspective on Asia expressed by Chilean traders and politicians from the saltpeter boom in Chile until the year before the outbreak of the US-Japan war. Informed by sources found in Chilean repositories, we identify that Chilean economic and diplomatic actors explored and got to know Asian markets and societies, reflecting pragmatism in seeking economic benefits in the relationship and at the same time an ambivalence in the cultural and political valuation given to the new trading partners.